Theory of planned behavior dan Stigma Publik sebagai Prediktor Perilaku Mencari Bantuan - Zakiya Ali; Istar Yuliadi; Rini Setyowati (UNS Press, 2023)
Abstract. The purpose of this study was to predicting help seeking behavior from profesional with theory of planned behavior and publik stigma of mental illness. The research subject were 397 college students. The method of data collection uses the scale of attitudes (α = 0,889), subjective norms (α = 0,901), perceived behavioral control (α = 0,748), intention (α=0,951), and public stigma of mental illness (0,913). The results of data analysis using path analysis showed that, intention was affected by attitudes (β = 0.445), subjective norms (β = 0.179), and publik stigma (β = -0.092). Meanwhile, perceived behavioral control has no effect on intention. Furthermore, help-seeking behavior is directly influenced by publik stigma (β = -0.104), but it is not influenced by intention so, it can be concluded that attitudes, subjective norms, perceptions of behavioral kontrol, and publik stigma cannot indirectly predict behavior with intention as mediator. Keywords: help-seeking behavior, theory of planned behavior, public stigma of mental disorder